FROM THE EDITORS - Esterhuyse, Abel; Liebenberg, Ian (Scientia Militaria - South African Journal of Military Studies, 2011)
Craig A. Snyder, in a book titled Contemporary Security and Strategy, noted that the broad idea of security provides strategic studies with institutional status and political legitimacy. Yet, the military core endows strategic studies, as a scholarly discipline, with intellectual coherence.1 This edition of Scientia Militaria, the South African Journal of Military Studies, reflects this reality with a very broad range of articles – from sexual behaviour and poetry to military intervention. Yet, the underlying commonality is an emphasis on military issues.